Answer:
what question ?
Step-by-step explanation:
i did not get it what question?
Answer:
The third picture
Step-by-step explanation:
Solve for x in both equations
2x<6
Divide both sides by 2:
x<3
3x+2>-4
Subtract 2 from both sides:
3x>-6
Divide both sides by 3:
x>-2
There is this trick you can use when x is on the left side of the equation to find out which way to shade in you graph. Keep in mind this is only for the left side, it will not work if your variable is on the right.
When the symbol is facing left < then shade left, imagine it is pointing which way to shade. x<3 is represented by the 3 picture on the left. When the symbol is facing right > then shade right, again it is pointing which way to shade. x>-2 is represented by the 3 picture on the right.
The circles are not filled in because the symbol is < and > rather than
. When it is greater than or equal to or less than and equal to (represented by the line under the symbol), then the circle is shaded in.
Answer:
arc BC = 84 degrees
Step-by-step explanation:
notice:
need to find n before finding arc BC
(13n -16) + (7n + 12) + 6n = 360
13n + 7n + 6n - 16 + 12 = 360
26n - 4 = 360
26n = 364
n = 364/26 = 14
so arc BC = 6*14 = 84 degrees
Answer: yes they have a proportional relationship
Step-by-step explanation:
Ratios are proportional if they represent the same relationship. One way to see if two ratios are proportional is to write them as fractions and then reduce them. If the reduced fractions are the same, your ratios are proportional.
Step one : let us test say c=1
F=9/5*1+32
F=9/5+32
F=1.8+32
F=33.8
Say c=2
F=9/5*2+32
F=9/10+32
F=0.9+32
F=32.9
Observe that as c increases
F reduces Hence they have a proportional relationship
-<em><u>samuelonum1</u></em>-
Not my answer/ please give brainlist
f^-1(x) = sq.rt 5(x - 10)/5, sq.rt 5(x - 10)/5 is the inverse of y = 5x^2 +10
Step-by-step explanation:
interchanging the variables
x = 5y^2 + 10
5y^2 +10 = x
5y^2 = x - 10
dividing by 5
5y^2/5 = x/5 + -10/5
y^2 = x/5 + - 10/5
y^2 = x/5 - 2
y = 5 (x-10) 0/5 (sq.rt)
g(5x^2 + 10) = 5x/5
g(5x^2 + 10) = x
f^-1(x) = sq.rt 5(x - 10)/5, sq.rt 5(x - 10)/5 is the inverse of y = 5x^2 +10